Education decentralization in the Omaheke Region of Namibia - Semba, Pecka (Rhodes University, Faculty of Education, Department of Education, 2007)
Before the attainment of independence on 21 March 1990, the people of Namibia were engaged in a protracted struggle against colonialism, racism and apartheid, all of which had denied the majority of the people democracy and development. The people of Namibia therefore did not have power to make decisions on matters that affect their lives and were also not able to determine their own destiny (Ministry of Regional Government and Housing [MoRGH]: 1998:1). After independence, the Namibian government provided for a policy of decentralization under Chapter 12 of the Constitution. After adopting decentralization as state policy in 1996 the government, under the auspices of the Ministry of Regional, Local Government and Housing, embarked upon an implementation process that began in 2003. Education decentralization was included in this process. As my research investigated participants' experience of education decentralization in the Omaheke Region, I conducted an interpretive case study. I employed semi-structured interviews as my main data collection instrument. The quality of my research lies mostly in the authenticity of my thick descriptions where I rely to a large degree on a high ratio of participant to researcher voice. The study has revealed that there is a basic understanding of what education decentralization refers to. Education decentralization is also perceived to provide for the democratization of education through the active participation of all relevant stakeholders - parents, teachers, learners and civil servants - in the education process. However, although there is a basic understanding of what education decentralization entails, there is not necessarily acceptance. The study revealed that many people in Omaheke have reservations about the process of decentralizing education services. Some regard education decentralization as central government "dumping" its responsibility on the Regions. Furthermore, neither the Regional Council, the Regional Education Office, schools, communities nor parents have the capacity to cope with decentralization. The responsibility for overseeing the implementation of decentralization in the Region lies with the Omaheke Regional Council. Education as a decentralized function ought to resort directly under the Regional Council. However, the Regional Education office does not yet operate under the Regional Council. Instead the Education Director continues to report directly to the Permanent Secretary of the Ministry of Education in the capital. In this way an important decentralization structure, the Regional Council, is bypassed and rendered toothless. The data reveal that there is only partial evidence of psychological and structural readiness for education decentralization. Consequently there is little meaningful participation and therefore no sense of ownership among parents, teachers, learners, community-based organizations and political leaders.
Keywords: Education -- Namibia; Schools -- Decentralization -- Namibia; Education and state -- Namibia; Educational change -- Namibia